FUNCTIONAL AND LOGICAL DESIGN OF THE HARDWARE OF THE CYBER-PHYSICAL WATER - HOVORUSHCHENKO, TETYANA; VOICHUR, YURII; KOLESNIK, MAKSIM; BALAN, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study analyzed the principles of constructing a cyber-physical system for monitoring water conditions, justified the selection of electronic components, sensors, controllers, and communication devices, and developed a prototype device that operates in autonomous mode. The key aspects of the development are energy efficiency, measurement accuracy, modularity, and system adaptability. A full-fledged virtual model of the device based on the Arduino Uno microcontroller, which acts as the central computing and control element of the system, has been successfully implemented. The interactive online environment Tinkercad was chosen to simulate physical processes and the interaction of electronic components. The key functional modules of the virtual device are virtual potentiometers that simulate analog signals from sensors. An informative liquid crystal display (LCD 16x2) with an I2C interface, which provides convenient and efficient output of text and numerical information, is also an integral part of the virtual system. The system also actively uses LEDs of different colors (red, blue, green) as visual indicators of exceeding the set thresholds for controlled parameters, which allows you to quickly assess the state of the aquatic environment. All components are connected via a virtual breadboard, which allows for convenient organization of a common power bus and ensures effective interaction between modules without soldering. The results of the system’s operation obtained during the simulation clearly demonstrate its ability to respond quickly to changes in parameter values simulated by potentiometers by activating the corresponding LEDs (green for normal status, red/blue for warning) and updating the information on the display screen.